KERAGAMAN JAMUR TERBAWA BENIH PADA EMPAT VARIETAS BENIH PADI ASAL PRODUSEN BENIH PADI DI LAMPUNG - Nurdin, Muhammad; Kusuma, Arvi Yuniar; Ermawati, Ermawati; Maryono, Tri (Jurnal Agrotek Tropika, 2023)
Seed quality is the main factor to gain optimal yields. The presence of fungi in seeds can cause damage to seeds, decrease germination and seed vigor, and cause disease in plants. The aim of this study was to detection of fungi in four varieties of rice seeds from local seed producers in Lampung. The rice seeds of Ciherang, Ciliwung, Cilamaya Muncul, and Inpari 42 varieties were obtained from the Center for Seed Certification for Food Crops and Horticulture in Lampung Province. Fungal detection in rice seeds was carried out using three methods, namely the washing method, blotter test, and agar plate test. The results showed that on four varieties of rice seeds tested was found five genera of fungi, i.e. Fusarium, Rhizoctonia, Curvularia, Rhizopus, and Aspergillus. In the washing method, Fusarium, Curvularia, and Aspergillus fungi were found. In the Blotter test method and the agar plate, Rhizoctonia, Curvularia, Rhizopus, and Aspergillus fungi were found. All of five fungi were found in Ciherang and Ciliwung seed. Rhizopus were not found in Inpari 42 seeds. Fusarium and Curvularia was not found in Cilamaya Muncul seeds. The Inpari 42 were the seeds with the highest number of fungi found and the lowest number of normal germinating seeds. The Cilamaya Muncul were the seeds with the least number of fungi found.